A case of subcutaneous metastatic malignant melanoma of the left medial ankle: a case report and review of literature - Lauren Workman; Lauren Fang; Martina Blazevic; Joanna Chen; Richard Simman (Journal of Medical Case Reports)
Abstract Background Although rare, melanoma confined to the dermis or subcutaneous tissue without evidence of a primary cutaneous site should provoke consideration of melanoma of unknown primary. This diagnosis carries a favorable prognosis when compared with cutaneous metastatic melanoma. Several hypotheses have been proposed for how melanoma of unknown primary develops, two of which were considered in our patient case: (1) spontaneous regression of the primary tumor following metastasis or (2) the traumatic implantation of ectopic melanocytic cells in other tissues, such as the subcutaneous tissue. Although not a true example of melanoma of unknown primary, our case is still noteworthy as it represents a unique instance of melanoma presenting subcutaneously from trauma to a preexisting epidermal nevus. Case presentation We present the case of a 66-year-old non-Hispanic Caucasian male who initially sought evaluation for a nontender lump of the left groin. Ultrasound-guided needle biopsy demonstrated stage III malignant melanoma. Upon further history taking, it was discovered that he had a nevus of the left medial ankle that was subjected to traumatic removal. He later developed a subcutaneous nodule at the same site. Positron emission tomography scan results supported the histopathologic findings which demonstrated invasive melanoma centered in the subcutaneous tissue without an epidermal component. Following left inguinal lymph node dissection, the patient received adjuvant immunotherapy and radiation to the left inguinal area. At 6 months following completion of therapy, metastases were identified in the lungs, vertebra, ribs, and liver. The patient is currently receiving immunotherapy with ipilimumab-nivolumab. Conclusion As our patient did not have a readily apparent primary epidermal melanoma site at presentation, consideration was given as to whether this case may represent a melanoma of unknown primary, as originally defined by Das Gupta. This case does not meet the proposed criteria, however, as the patient reported a preexisting nevus in the area that was subjected to traumatic removal. Instead, we postulate that this trauma allowed for implantation of melanocytes into the subcutaneous tissue that later resulted in a malignant melanoma.